Vein-Supercharged Peroneal Artery Perforator Propeller Flap for Achilles Soft Tissue Coverage - Atmodiwirjo, Parintosa; Supit, Laureen (Jurnal Plastik Rekonstruksi, 2013)
Background: Wounds on the distal third of the lower extremity are reconstructively challenging, as there is lack of spare local tissue to design local flaps from. The perceived alternative is to perform free flaps to cover for these defects. Drawbacks include the need for specific training to perform microsurgery, longer time required, and the probable bulkiness when donor is obtained from certain areas. The perforator propeller flap is a local island fasciocutaneous flap, designed with 2 blades of skin island of unequal length extending from each side of the perforator. As the flap is rotated, the longer blade will cover the defect. Patient and Method: A case of soft tissue defect on the achilles is reported, with successful defect closure by utilizing a peronal artery perforator based fasciocutaneous propeller flap with 180 degree rotation and vein supercharge to facilitate backflow. Secondary defect required split-thickness skin grafting. Result: After surgery, muscles of the lower limb started to swell and get compromised. We removed some stitches to allow soft tissue expansion underneath the flap. after the release, flap perfusion improved. Stitches were left open for 3 days, then closure of flap edges by placing gradual traction sutures which were tightened daily. By the 7th day, flap edges was re-approximated and the skin grafts took well. Summary: The ability of the propeller flap to rotate makes this flap highly useful and versatile for the reconstruction of distal lower limb defects. Flap dimension can be enhanced when distal part of the flap is supercharged to neighboring recipient vessels. Another advantage is the close vicinity of donor, giving better aesthetic result.6